Population ageing in a small open economy: some policy experiments with a tractable general equilibrium model - Juha Kilponen; Helvi Kinnunen; Antti Ripatti (Bank of Finland, 2006)
This paper extends Gertler's (1999) tractable overlapping generations model with life-cycle features by allowing for distortionary taxation, demographic transition and stochastic variation in demographic structure.The model is then used to study demographic change in the small open economy of Finland. Simulations highlight the key role played by labour market responses to ageing.When the responses of labour supply, wages, and hence private consumption, to higher taxation are consistently accounted for, population ageing has clearly much larger effects on public finance, when compared to mechanical sustainability calculations.Stochastic simulations suggest that lengthening of working time has only a modest alleviating effect on the fiscal burden of ageing.This is due to the fact that stochastic variation in the length of working time has only a relatively small effect on the model's dependency ratio.Variation in life expectancy is clearly much more important.
URN:NBN:fi:bof-20140807536
Keywords: E13; H55; J11; J26; 330; ageing; general equilibrium; public finance; demographic uncertainty